A Process for Using Oxide TFTs over LTPS TFTs for OLED‐TV Manufacturing. Issue 6 (1st November 2015) - Cunningham, Kerry L.
Abstract : Technical solutions for the fabrication of large‐scale OLED displays include new manufacturing equipment and processes developed by Applied Materials.